Association between haemodynamics during cardiopulmonary resuscitation and patient outcomes. (January 2022) - Koyama, Yasuaki; Matsuyama, Tasuku; Inoue, Yoshiaki
Abstract: Aim: There is no defined target for blood flow during chest compressions (CC). We previously reported various haemodynamic patterns in which dominant arterial and venous pressures were observed during CC. This study aimed to evaluate arterial and venous perfusion pressures during CC and determine their association with patient outcomes. Methods: In this prospective observational single-centre study, arterial and venous pressures were recorded continuously on arrival at the emergency department for patients with non-traumatic out-of-hospital cardiac arrest. Parameters included multiple pressure measurements: the arterial systolic (A sys), mean (A mean), and diastolic (A dias); the venous systolic (V sys), mean (V mean), and diastolic (V dias); and the differences between arterial and venous systolic (ΔSys A-V), mean (ΔMean A-V), and diastolic (ΔDias A-V). We compared patients with and without return of spontaneous circulation (ROSC). Results: Among 50 patients, 16 (32%) had ROSC. Of the total measurement time, average A sys, A dias, ΔSys A-V, ΔDias A-V, A mean, and ΔMean A-V were significantly higher in patients with ROSC. When the average ΔMean A-V was stratified, there were 19 (38%) patients with negative average ΔMean A-V values, none of whom had ROSC. As the average ΔMean A-V increased, the ROSC rate also increased (p = 0.00002). Conclusions: ROSC did not occur in patients with negative average ΔMean A-V values. ROSC may be achieved through individualised resuscitation that places a greater emphasis on differences between mean arterial and venous pressure, rather than through uniform resuscitation.